2022
DOI: 10.3390/ijms231912038
|View full text |Cite
|
Sign up to set email alerts
|

CircCSDE1 Regulates Proliferation and Differentiation of C2C12 Myoblasts by Sponging miR-21-3p

Abstract: The growth and development of skeletal muscle is regulated by many factors, and recent studies have shown that circular RNAs (circRNAs) can participate in this process. The model of porcine skeletal muscle injury was constructed to search for circRNAs that can regulate the growth and development of skeletal muscle in pigs. Using whole-transcriptome sequencing and bioinformatics analysis, a novel circRNA (circCSDE1) was screened out, which is highly expressed in skeletal muscle. Functional studies in C2C12 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Through bioinformatics analysis, the circRNA/lncRNA-miRNA-mRNA regulatory network was constructed, which was centered on HMG20B , MYOG , MYF6 and MYOD1 , involved in the regulation of skeletal muscle fiber type transformation after birth. Sun et al reported the ceRNA network of miR-21-3p/CDK16 mediated by circCSDE1, which regulates pig muscle development ( Sun et al, 2022 ). Li et al constructed the regulatory network of porcine skeletal muscle differentiation with circIGF1R/miR-16/mRNA through sequencing and bioinformatics analysis ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through bioinformatics analysis, the circRNA/lncRNA-miRNA-mRNA regulatory network was constructed, which was centered on HMG20B , MYOG , MYF6 and MYOD1 , involved in the regulation of skeletal muscle fiber type transformation after birth. Sun et al reported the ceRNA network of miR-21-3p/CDK16 mediated by circCSDE1, which regulates pig muscle development ( Sun et al, 2022 ). Li et al constructed the regulatory network of porcine skeletal muscle differentiation with circIGF1R/miR-16/mRNA through sequencing and bioinformatics analysis ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that CDR1as could induce the differentiation of porcine myoblasts by adsorbing miR-7 and up-regulating the expression of IGF1R ( Li et al, 2019 ). By sequencing the longissimus dorsi muscle of Jinfen pig, Sun et al discovered that circCSDE1 regulated the expression of CDK16 by binding to miR-21-3p, and verified on C2C12 that circCSDE1 promoted myoblast proliferation and inhibited myoblast differentiation ( Sun et al, 2022 ). Li et al examined that circIGF1R promoted the differentiation of porcine myoblasts by adsorbing miR-16 regulatory gene expression ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique biochemical characteristics, researchers can better understand the metabolism and differentiation of skeletal muscle at cellular and molecular levels [ 20 ]. Sun et al [ 21 ] identified circCSDE with a stable and high expression in porcine skeletal muscle and studied the function of circCSDE on C2C12 cells, where they found that circCSDE1 and its target miR-21-3p jointly regulated the proliferation and differentiation of myoblasts. In their study, the mechanism of circCSDE regulating the growth and development of skeletal muscle in the porcine skeletal muscle injury model was verified.…”
Section: Discussionmentioning
confidence: 99%
“…Sun constructed a pig skeletal muscle injury model and screened out the differentially expressed circRNA circ-SCDE1. Because it is highly conservative in pigs and mice, C2C12 was used to verify the specific mechanism of circCSDE1 regulating the proliferation and differentiation of myoblasts [32]. Ma identified and predicted circRNA in Duroc pigs with different daily weight gain [33].…”
Section: Introductionmentioning
confidence: 99%